Risk Factors for Recidivism in Juvenile Criminal Offenders - Dimitrijoska, Suncica; Gordana , Buzarovska; Zorica Saltirovska (European Journal of Social Science Education and Research, 2019)
In the Republic of Macedonia, very few authors are actively working on classification, evaluation, and criteria for choice of treatment of juvenile delinquents, while others are working on the evaluation of the treatment and implementation of new forms and types of interventions. On the one hand, the imperfect intervention models, and on the other hand, inadequate scientific methodology, are oftentimes factors contributing to a state which leads to problems and intervention models that are created and evaluated in one socio-cultural environment, and implemented in another environment, much more different to the former. The penological analysis of recidivism is concerned with two types of factors, such as inadequate social reaction – an improper criminal sanction, and inadequate treatment and unsuccessful process of resocialization, i.e. inadequate treatment in the facility where the sanction is being endured (Boshkovic, M., 2006). The abundance of studies conducted on the topic have all shown that the lack of parental support and mutual trust are closely correlated to the phenomenon of juvenile delinquency, which in time could lead to re-offending and recidivism. The focus of the current study is to validate the assessment instrument used by the Department of Juvenile Justice to determine a referred youth’s risk to re-offend.